Vulnerability to unintentional injuries associated with land-use activities and search and rescue in Nunavut, Canada - Clark, Dylan; Ford, J; Pearce, T; Berrang Ford, L (ArcticNet Inc., 2016)
Injury is the leading cause of death for Canadians aged 1 to 44, occurring disproportionately across regions and communities. In the Inuit territory of Nunavut, unintentional injury rates are over three times the Canadian average. In this study, we develop a framework for assessing vulnerability to injury and use it to identify and characterize the determinants of injuries on the land in Nunavut. We specifically examine unintentional injuries on the land (outside of hamlets) because of the importance of land-based activities to Inuit culture, health, and well-being. Semi-structured interviews (n=45) were conducted in three communities that have varying rates of search and rescue (SAR), complemented by an analysis of SAR case data for the territory. We found that risk of land-based injuries is affected by socioeconomic status, Inuit traditional knowledge, community organizations, and territorial and national policies. Using the Vulnerability to Injury Framework we were able to analyze the impact of these factors on safety. Socioeconomic status emerged as a root or distal factor to land safety at an individual and community scale, affecting the sensitivity of individuals, influencing the condition of machinery, the amount of gear an individual had, and the level of land-use they could afford. The ability to adapt to hazards and the changing Arctic environment was also found to be affected by socio-economic status, influencing the ability to purchase new protective technologies, community resources for prevention efforts, and emergency response resources. Notably, by moving beyond common conceptualizations of unintentional injury, we are able to better assess root causes of unintentional injury and outline paths for prevention.